The East African Court of Justice and Human Rights Jurisdiction: Drawing the Line (Strathmore Law Review, 2018)
Human rights in Africa have gradually gained a place of recognition few could have foreseen only a decade ago. With the promotion and protection of human rights entrenched deep in the African Charter on Human and Peoples’ Rights, African states have a duty to uphold this principle in the larger goal of regional economic integration. The East African Court of Justice (EACJ), a regional court, has thus assumed the role of a watchdog in breathing life into these provisions, safeguarding the rule of law and ensuring everyone plays by the rules. It is unfortunate that these watchdogs can then lack the most important tool in steering the ship – jurisdiction. This paper, through a detailed analysis of literature review, tackles the pertinent question of whether the court has jurisdiction to handle human rights cases and arrives at the conclusion that an express mandate is lacking, but there is a somewhat implied mandate. Nonetheless, a clear articulation of the EACJ’s mandate is necessary to enable it to address issues effectively and efficiently.